Identification and characterization of Pichia membranifaciens Hmp-1 isolated from spoilage blackberry wine - Ying WANG; Yan-cun ZHAO; Lin-lin FAN; Xiu-dong XIA; Ya-hui LI; Jian-zhong ZHOU (Journal of Integrative Agriculture, 2018)
The pellicle-forming yeast could cause the quality deterioration of wine. In this study, a pellicle-forming strain Hmp-1 was isolated from the spoilage blackberry wine, and identified as Pichia membranifaciens based on the morphology and partial nucleotide sequence of 26S rDNA. The effects of fermentation conditions (ethanol, sulfur dioxide, sugar, and temperature) on the growth of P. membranifaciens strain Hmp-1 and Saccharomyces cerevisiae strain FM-S-115 (a strain used for the blackberry wine fermentation) were investigated, respectively. The results indicated that Hmp-1 had lower resistance to these factors compared to FM-S-115, and the growth of Hmp-1 was completely inhibited by 10% (v/v) or 50 mg L–1 SO2 during the fermentation of blackberry wine. These results suggested that Hmp-1 could effectively be controlled by increasing ethanol or SO2 concentration during the fermentation and storage of blackberry wine. Furthermore, the analysis based on gas chromatography-mass spectrometry (GC-MS) showed that Hmp-1 remarkably decreased kinds of volatile compounds in blackberry wine, especially aldehydes and esters. In addition, some poisonous compounds were detected in the blackberry wine fermented by FM-S-115 and Hmp-1. These results suggested that Hmp-1 was a major cause leading to the quality deterioration of blackberry wine.